2017
DOI: 10.1111/all.13150
|View full text |Cite
|
Sign up to set email alerts
|

Allergenome characterization of the mosquito Aedes aegypti

Abstract: The newly identified allergens may play a role in the pathophysiology of mosquito allergy in the tropics, and some of them might be important arthropod-related proteins involved in cross-reactivity between A. aegypti and other allergenic arthropods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
(57 reference statements)
0
26
0
1
Order By: Relevance
“…This supports the shift to recombinant salivary components for the study of cat flea hypersensitivity. In any case, proteomic characterization of cat flea extract yielded interesting information for other respiratory allergic diseases that could by induced by insect inhalation [30-33]. The C. felis extract was found to be rich in muscle-skeletal proteins such as tropomyosin, ankirins, and troponins, which are usually highly conserved in invertebrates and have been reported as allergenic in several sources of epidemiological importance such as house dust mites, cockroaches, and mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the shift to recombinant salivary components for the study of cat flea hypersensitivity. In any case, proteomic characterization of cat flea extract yielded interesting information for other respiratory allergic diseases that could by induced by insect inhalation [30-33]. The C. felis extract was found to be rich in muscle-skeletal proteins such as tropomyosin, ankirins, and troponins, which are usually highly conserved in invertebrates and have been reported as allergenic in several sources of epidemiological importance such as house dust mites, cockroaches, and mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…6 HDM and mosquitoes are evolutionarily related as part of the Phylum Arthropoda. 8,9 We previously demonstrated that natural and recombinant A. aegypti tropomyosins cross-react with tropomyosin from HDM. 8,9 We previously demonstrated that natural and recombinant A. aegypti tropomyosins cross-react with tropomyosin from HDM.…”
mentioning
confidence: 99%
“…6 HDM and mosquitoes are evolutionarily related as part of the Phylum Arthropoda. The mosquito species Aedes aegypti is also a source of several allergens [6][7][8][9] and contains Aed a 10 (tropomyosin). 8,9 We previously demonstrated that natural and recombinant A. aegypti tropomyosins cross-react with tropomyosin from HDM.…”
mentioning
confidence: 99%
“…Allergic reactions to mosquito bite are underestimated due to the current lack of reliable diagnostic tools. Both “species-specific” and cross-reactive allergenic molecules have recently been described mainly in the saliva of yellow fever mosquito ( Aedes aegypti ), Asian tiger mosquito ( Aedes albopictus ), Aedes vexans , and Culex quinquefasciatus [2-4]. Few studies have been conducted on Aedes communis (Ac) [5, 6], and no Ac molecule has been registered to date in the WHO/IUIS database [7].…”
mentioning
confidence: 99%
“…1), suggesting the lack of some relevant allergenic molecules in extracts for in vitro diagnosis [2, 9]. IgE specific for Aedes and Tabanus were also significantly associated (OR: 9 [CI: 1.3–61.1], p < 0.02), as well as MUXF3 reactivity (OR: 2.9 [CI: 1.1–8.5], p = 0.03), suggestive of the presence of cross-reactive glycans (CCD) in mosquito extracts [10].…”
mentioning
confidence: 99%